Operative Versorgungskonzepte für Menschen mit Varianten der Geschlechtsentwicklung - Stein, Raimund; Krege, Susanne (Monatsschrift Kinderheilkunde, 2019)
As a rule surgical treatment of the genitalia is not indicated in newborn children. When possible and meaningful, every surgical treatment should be delayed until the time when the individual is capable of reasoning or able to give consent. In cases of anatomically founded medical problems operative measures can be necessary even in childhood and adolescence. Planning of surgical treatment in differences of sex development (DSD) is oriented to the appearance and function of the genitalia and the possibility of fertility in later life. The operative treatment of people with DSD should only be carried out by experienced surgeons, who are familiar with the wide variety of techniques and coping with complications. A lifelong aftercare with competent contact persons must be guaranteed.